Global Trends in Computational Thinking Research in Physics Learning: A Systematic Literature Review - Diraya, Inayatun; Kusairi, Sentot; Parno, Parno (Jurnal Ilmiah Pendidikan Fisika, 2025)
This research examines the global trends regarding applying computational thinking (CT) in physics learning through a Systematic Literature Review (SLR) approach. By analyzing 30 selected articles published in 2019-2024, this study aims to provide insight into the types of research, subjects, instruments, physics materials, and supporting media used. The results showed that most studies focused on developing CT-based learning products, such as interactive modules and simulations, which were predominantly applied to high school students with materials such as electricity, temperature, and heat. Frequently used media include Scratch, Arduino, and Visual Python, which are proven to improve students' critical thinking, collaboration, and algorithmic skills. However, CT implementation is faced with challenges such as limited technology facilities, teacher training needs, and the complexity of curriculum integration. This research recommends the exploration of problem-, project-, and game-based learning approaches to support the development of CT at different levels of education. The results are expected to be the basis for developing more innovative and effective learning strategies to face the challenges of the 21st century.